A sodium ion positive electrode material and its preparation method and application
By building an oxygen-depleted layer on the surface of the sodium ion layered oxide positive electrode material, the structural transition from layered oxide to the rock salt phase is achieved, the material structural instability and interface problems are solved, and the material's magnification and cyclic performance are significantly improved.
Patent Information
- Application Number
- CN202211328970.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-10-27
AI Technical Summary
The existing sodium ion layered oxide positive electrode materials have unstable structure during the circulation process, resulting in low rate performance and cyclic performance, and serious interface problems between the cladding and the positive electrode materials, affecting ionic conductivity.
The oxygen-depleted layer is constructed on the surface of the sodium ion layered oxide positive electrode material, and the gradual transition from the layered oxide to the rock salt phase from the inside to the outside is achieved, so that the cladding layer is closely combined with the layered oxide body material, reducing the formation of the interface and prevent oxygen loss.
It improves the structural stability of sodium ion positive electrode material, improves the rate performance and cycling performance, and extends the cycling stability of the battery.
Smart Images

Figure CN115472820B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sodium ion positive electrode material and a preparation method and application thereof. Background Art
[0002] With the development and progress of technology, lithium batteries have been widely used in energy storage, electric vehicles, consumer electronics and other fields, and have become an indispensable part of human life. However, due to the limited reserves of common resources for lithium batteries such as lithium and nickel, the price of lithium battery raw materials has continued to rise in recent years, which has seriously reduced the cost-effectiveness of lithium batteries and affected the application of lithium batteries. In addition, due to people's continuous pursuit of lithium battery energy density, the safety of lithium batteries has also become a hot topic of concern.
[0003] Compared with lithium batteries, the reserves of sodium are much higher than lithium. With the continuous maturity of technologies such as seawater sodium extraction, the price of sodium will continue to fall, which is also the inherent price advantage of sodium batteries. Lithium batteries are prone to short-circuit and spontaneous combustion due to the easy generation of dendrites, while sodium batteries are not easy to form dendrites and are much safer than lithium batteries. Taking all factors into consideration, although the energy density and power density of sodium batteries are lower than those of lithium batteries, due to their unique advantages, sodium batteries have great potential to fill the market gap between lithium batteries and lead-acid batteries. At present, the commercialized negative electrode materials of sodium batteries are mainly hard carbon, etc., and the positive electrode materials are mainly divided into Prussian, polyanion, oxide, etc. Among them, polyanion positive electrode materials have higher specific capacity and cycle performance, but the conductivity of polyanion materials themselves affects their rate performance and cycle performance. How to improve the conductivity of polyanion positive electrode materials has become the key to promoting their application. This patent can be applied to the surface coating of positive electrode materials of sodium batteries and lithium batteries to improve conductivity and improve the electrochemical properties of positive electrode materials.
[0004] At present, nickel-manganese-based layered oxides, NaNi x M y Mn z O2 (M=Co, Fe, etc.) is attracting widespread attention. Similar to high nickel oxide positive electrode materials in lithium batteries, the gram capacity of the oxide is directly related to the Ni content. Increasing the Ni content can effectively increase the specific capacity of the oxide positive electrode material. However, during the cycle, too high Ni content will directly affect the stability of the layered oxide structure. 4+It has high activity in the electrolyte. When the Ni content is higher than 60%, the cycle stability of the material will be significantly reduced. In addition, when the voltage is higher than 4.0V, a series of side reactions between the layered oxide and the electrolyte will further accelerate the attenuation of material performance. In lithium battery applications, an effective strategy to effectively alleviate the problem of poor cycle stability caused by high nickel content is to coat the surface of the material. Constructing a coating layer on the surface of the layered oxide material can separate the electrolyte from the layered oxide, effectively avoiding direct contact between the two, thereby reducing the occurrence of side reactions, inhibiting phase changes, and improving structural stability. This method of improving material performance is also used in sodium ion batteries.
[0005] For example, CN109524649A discloses a sodium ion battery positive electrode material with a coating structure, and a preparation method and application thereof, the method comprising: selecting / preparing a coating liquid; the coating liquid comprises a coating precursor composed of a metal salt and / or a hydrate thereof; placing the positive electrode material to be coated in a coating furnace, heating it to 200 to 1000 degrees, using compressed air or nitrogen or argon to carry the coating liquid into the coating furnace, the coating precursor is decomposed by heat to form an oxide, and is evenly coated on the surface of the positive electrode material; taking out the prepared positive electrode material with an oxide coating layer, thereby obtaining the sodium ion battery positive electrode material with the coating structure.
[0006] For another example, CN109638273A discloses a coating method for a positive electrode material of a sodium ion battery, comprising the following steps: step 100, sequentially adding a solvent, a positive electrode material and a coating precursor into a stirring tank, and uniformly mixing the solvent and the coating precursor by stirring; step 200, spray drying the above mixture through a spray drying device to obtain a positive electrode material coated with the coating precursor; step 300, secondary sintering the positive electrode material coated with the coating precursor to form an oxide shell, thereby obtaining an oxide-coated positive electrode material.
[0007] Common coating layer compounds include Al2O3, MgO, TiO2, AlF3, NaPO3, etc. Common coating methods include chemical method, ball milling method, atomic layer deposition technology, etc. However, it should be noted that due to the sensitivity of sodium positive electrode materials to moisture, most coating methods cannot be applied, or require further sintering, which increases the difficulty and cost of their application in sodium positive electrode materials. In addition, since the coating layer and the positive electrode material have different components and structures, the introduction of the coating layer will inevitably introduce interface problems between the coating layer and the positive electrode material, affecting its ionic conductivity. In addition, due to the different material structures, it is difficult to ensure that the coating layer material and the positive electrode material maintain the same expansion coefficient during the charge and discharge process, causing damage or shedding of the coating layer material.
[0008] Therefore, how to effectively coat the sodium ion layered oxide positive electrode material and at the same time improve the rate performance and cycle performance of the material is a technical problem that needs to be solved urgently. Summary of the invention
[0009] The purpose of the present invention is to provide a sodium ion positive electrode material and a preparation method and application thereof. The present invention constructs an oxygen-deficient layer on the surface of the sodium ion layered oxide positive electrode material, realizes a gradual structural transition from the layered oxide to the rock salt phase from the inside to the outside, makes the coating layer tightly combined with the layered oxide main material, reduces the formation of the interface, and can also prevent the further loss of oxygen inside the layered oxide, thereby improving the structural stability of the material, thereby improving the rate performance and cycle performance of the sodium ion positive electrode material.
[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a sodium ion positive electrode material, comprising a sodium ion layered oxide inner core and an oxygen-deficient layer located on the surface of the inner core, wherein the oxygen-deficient layer is a rock salt phase structure.
[0012] The present invention constructs an oxygen-depleted layer on the surface of the sodium ion layered oxide positive electrode material, realizes a gradual structural transition from the layered oxide to the rock salt phase from the inside to the outside, makes the coating layer tightly combined with the layered oxide main material, reduces the formation of the interface, and can also prevent the further loss of oxygen inside the layered oxide, thereby improving the structural stability of the material, thereby improving the rate performance and cycle performance of the sodium ion positive electrode material.
[0013] In the present invention, the oxygen-depleted layer is a rock salt phase structure, which can better improve the electrochemical performance of the material, effectively separate the bulk material from the electrolyte during the cycle, reduce or avoid the damage to the bulk material caused by side reactions occurring during the cycle, and play the role of a coating layer, thereby better improving the cycle stability of the positive electrode material of the sodium ion battery.
[0014] In the present invention, if the oxide material is directly coated on the surface of the sodium ion oxide, instead of constructing an oxygen-depleted layer in the present application, and the oxygen-depleted layer is in situ constructed on the surface of the sodium ion layered oxide, although the oxide material is directly coated on the surface of the sodium ion oxide positive electrode material can also improve the cycle performance of the bulk material to a certain extent, the oxide material cannot form a dense coating and cannot provide sufficient support and protection for the bulk material during the cycle. In addition, the coating of the oxide material on the surface cannot avoid the interface problems between the bulk material and the bulk material, and cannot improve the long-term cycle stability of the material.
[0015] Preferably, the chemical formula of the sodium ion layered oxide core is NaNi x M y Mn zO2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
[0016] For example, the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, the y may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, and the z may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.
[0017] In a second aspect, the present invention provides a method for preparing the sodium ion positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) mixing and coating a sodium ion hydroxide precursor with a polymer material to obtain a precursor of a surface-coated polymer material;
[0019] (2) Mixing the precursor of the surface-coated polymer material of step (1) with a sodium source, and sintering them in an oxygen-containing atmosphere to obtain the sodium ion positive electrode material.
[0020] The invention modifies the sodium ion hydroxide precursor material with a polymer material to form a composite structure with the polymer material. In the subsequent sintering process, the carbonization and oxidation process of the polymer will take away a part of the oxygen on the surface of the layered oxide material, resulting in rapid loss of oxygen in the structure and forming oxygen vacancies. Furthermore, when sintering is performed in an oxygen-containing atmosphere, no carbon will remain. Moreover, the rapid loss of oxygen on the surface of the sodium ion layered oxide will lead to a phase change from a layered structure to a rock salt phase, thereby realizing a gradual transition from the layered oxide to the rock salt phase from the inside to the outside, so that the coating layer is closely combined with the layered oxide main body material, reducing the generation of the interface, and the thickness of the phase change layer can be controlled within a range of about 10 nm, thereby in-situ constructing an oxygen-poor layer on the surface of the sodium ion layered oxide that is closely combined with the main body material and has a stable structure, thereby achieving the effect of improving the cycle stability.
[0021] In the present invention, if the polymer material is not coated and modified in the precursor stage, but is modified after the positive electrode material is obtained, the polymer material cannot form a dense coating, and cannot provide sufficient support and protection for the main material during the cycle. In addition, the polymer coating cannot avoid interface problems with the main material, resulting in the inability to improve the long-cycle stability of the material.
[0022] Moreover, the present invention coats the hydroxide precursor material (i.e., the precursor material prepared by the co-precipitation method) to form a uniform and continuous oxygen-deficient phase protective layer on the surface of the sample after sintering. However, if other precursors (such as carbonate precursors) or layered oxides prepared by pure solid-phase sintering are coated, a uniform and continuous protective layer cannot be formed.
[0023] Preferably, the chemical formula of the sodium hydroxide precursor in step (1) is Ni x M y Mn z (OH)2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
[0024] For example, the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, the y may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, and the z may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.
[0025] Preferably, the method for preparing the sodium ion hydroxide precursor in step (1) comprises:
[0026] A mixed salt solution of a nickel source, a manganese source and an M source, a precipitant solution and a complexing agent solution are added in parallel to carry out a coprecipitation reaction and age to obtain the sodium ion hydroxide precursor, wherein the M source includes any one of a cobalt source, an iron source, a copper source, a titanium source or a tin source or a combination of at least two thereof.
[0027] Preferably, the reaction temperature during the coprecipitation reaction is 40-60°C, such as 40°C, 45°C, 50°C, 55°C or 60°C.
[0028] Preferably, the rotation speed during the coprecipitation reaction is 800-1200 r / min, for example, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min or 1200 r / min.
[0029] Preferably, the pH value during the coprecipitation reaction is 8-10, such as 8, 8.5, 9, 9.5 or 10.
[0030] Preferably, the aging time is 3 to 7 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours or 7 hours.
[0031] Preferably, in step (1), the mass of the polymer material is 0 to 10% of the mass of the sodium ion hydroxide precursor and does not include 0%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% etc.
[0032] In the present invention, excessive mass of the polymer material will result in an excessively thick oxygen-deficient layer, which will affect the normal performance of the electrochemical properties of the bulk material (core).
[0033] Preferably, the elements in the polymer material include C and H.
[0034] Preferably, the elements in the polymer material further include O and / or N.
[0035] Preferably, the polymer material includes any one of urea, dopamine, glucose, sucrose or tannic acid, or a combination of at least two of them.
[0036] Preferably, the mass of the urea is 0-8% of the mass of the sodium ion hydroxide precursor and does not include 0%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8% etc.
[0037] Preferably, the mass of the dopamine is 2-6% of the mass of the sodium ion hydroxide precursor, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.
[0038] In the present invention, if too much dopamine is added, the thickness of the oxygen-depleted layer will increase, and a large amount of sodium carbonate will be formed on the surface of the material, affecting the electrochemical properties of the bulk material. If too little dopamine is added, a continuous and complete coating layer cannot be formed, affecting the final effect of improving the electrochemical performance.
[0039] Preferably, the mixed coated raw materials in step (1) also include a surfactant.
[0040] In the present invention, the surfactant makes it easier for the polymer to be evenly adsorbed on the surface of the precursor. If no surfactant is added, local aggregation of the polymer material will occur, affecting the continuity and integrity of the oxygen-depleted layer finally formed, and failing to provide complete and effective protection for the bulk material, thereby affecting the electrochemical properties of the material.
[0041] Preferably, the mass of the surfactant is 1-3% of the mass of the sodium ion hydroxide precursor, for example, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8% or 3%.
[0042] Preferably, the surfactant comprises polyvinyl pyrrolidone and / or cetyltrimethylammonium bromide.
[0043] Preferably, when a surfactant is included in the mixed coating process of step (1), the mixed coating comprises:
[0044] Firstly, a sodium ion hydroxide precursor is mixed with a surfactant, and then a polymer material is added for mixed coating.
[0045] When the present invention contains a surfactant during the mixed coating process, the surfactant is first used to modify the surface of the precursor material. The introduction of the surfactant can make the subsequently added polymer material form uniform adsorption on the surface of the precursor. If the polymer material and the surfactant are added at the same time, it will affect the uniform coating of the polymer material in the precursor, thereby resulting in the obtained oxygen-deficient phase coating being not uniform enough, affecting the improvement of the material's recycling performance; the precursor material after the mixed coating is mixed with a sodium source and sintered. During the sintering process in an oxygen-containing atmosphere, the surfactant and the adsorbed polymer material will undergo carbonization and subsequent oxidation reactions to generate CO2 or CO. During the oxidation process, the surfactant and the polymer material will take away a portion of oxygen from the surface structure of the precursor material, prompting the structure to be converted into a more stable oxygen-deficient phase. The generated oxygen-deficient phase can play a role similar to a coating layer due to its more stable structure, but this coating layer can directly form a gradual transition with the main material to avoid the cross-sectional problem caused by coating with different materials, and can also improve the stability during the cycle.
[0046] Preferably, the sintering in step (2) includes performing primary sintering and secondary sintering in sequence.
[0047] Preferably, the primary sintering temperature is 450-550°C, for example, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C.
[0048] Preferably, the temperature of the secondary sintering is 750-900°C, for example, 750°C, 780°C, 800°C, 830°C, 850°C, 880°C or 900°C.
[0049] As a preferred technical solution, the preparation method comprises the following steps:
[0050] (1) adding a mixed salt solution of a nickel source, a manganese source and an M source, a precipitant solution and a complexing agent solution in parallel, performing a coprecipitation reaction at 40 to 60° C. and a rotation speed of 800 to 1200 r / min, wherein the pH value during the reaction is 8 to 10, and aging is performed for 3 to 7 hours to obtain a sodium ion hydroxide precursor;
[0051] Firstly, a sodium ion hydroxide precursor is mixed with a surfactant, wherein the mass of the surfactant is 1 to 3% of the mass of the sodium ion hydroxide precursor, and then a polymer material is added for mixed coating, wherein the mass of the polymer material is 0 to 10% of the mass of the sodium ion hydroxide precursor but does not include 0%, to obtain a precursor with a surface coated with the polymer material;
[0052] (2) mixing the precursor of the surface-coated polymer material of step (1) with a sodium source, and sequentially performing primary sintering and secondary sintering in an oxygen-containing atmosphere to obtain the sodium ion positive electrode material;
[0053] Wherein, the chemical formula of the sodium hydroxide precursor in step (1) is Ni x M y Mn z (OH)2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
[0054] In a third aspect, the present invention further provides a sodium ion battery, comprising the sodium ion positive electrode material as described in the first aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The sodium ion positive electrode material provided by the present invention realizes a gradual structural transition from the layered oxide to the rock salt phase from the inside to the outside, so that the oxygen-poor coating layer is closely combined with the layered oxide main body material, reducing the formation of the interface, and can also prevent the further loss of oxygen inside the layered oxide, thereby improving the structural stability of the material, thereby improving the rate performance and cycle performance of the sodium ion positive electrode material. When the battery adopts the sodium ion positive electrode material provided by the present invention, the amount of dopamine added is 2-6% of the mass of the sodium ion hydroxide precursor, or the amount of urea added is 0-8% of the mass of the sodium ion hydroxide precursor and does not include 0%, the capacity retention rate after 100 cycles at 0.5C can reach more than 80.3%, and the capacity retention rate after 300 cycles at 2C can reach more than 59.6%.
[0057] (2) The present invention modifies the sodium ion hydroxide precursor material with a polymer material to form a composite structure with the polymer material. During the subsequent sintering process in an oxygen-containing atmosphere, the carbonization and oxidation process of the polymer will in situ construct an oxygen-deficient layer on the surface of the sodium ion layered oxide that is tightly combined with the base material and has a stable structure, thereby achieving the effect of improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Schematic diagram of the formation process of the sodium ion positive electrode material provided in Example 1. DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Example 1
[0061] This embodiment provides a sodium ion positive electrode material, the positive electrode material comprises a sodium ion layered oxide core and an oxygen-deficient layer located on the surface of the core, the chemical formula of the sodium ion layered oxide core is Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2, the oxygen-depleted layer has a rock salt phase structure and is in situ constructed on the surface of the layered oxide, that is, the oxygen-depleted layer is an oxygen-depleted phase containing Na, Ni, Fe and Mn.
[0062] The preparation method of the sodium ion positive electrode material is as follows:
[0063] (1) The sulfates corresponding to the required elements (NiSO4, MnSO4, FeSO4) are divided into Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2 is dissolved in a solution in a stoichiometric ratio, which is marked as solution A; a NaOH solution (precipitant solution) and an ammonia solution (NH3·H2O) solution (complexing agent solution) are prepared; solution A, the precipitant solution and the complexing agent solution are added to a continuous reactor in parallel, the pH value during the reaction is controlled to be 8.5, a coprecipitation reaction is carried out at a reaction temperature of 50°C and a rotation speed of 1000r / min, the solution after the reaction is aged for 5h, and the target precursor Ni is obtained after multiple washings with deionized water and drying. 0.6 Fe 0.25 Mn 0.15 (OH)2;
[0064] (2) 100g of precursor Ni 0.6 Fe 0.25 Mn 0.15 (OH)2 was dispersed in water, 3 g of polyvinyl pyrrolidone (PVP) was added, ultrasonicated for 20 min, then stirred for 25 min, dopamine was added (the amount of dopamine added was 3% of the precursor material), stirred for 5 h, filtered, and dried in a drying oven at 80 ° C for 10 h to obtain a dopamine-coated precursor material;
[0065] (3) The precursor material in step (2) is uniformly mixed with Na2CO3 according to a stoichiometric ratio, sintered at 450°C for 5 hours in an oxygen atmosphere, and then heated to 900°C for a second sintering for 20 hours to obtain the sodium ion positive electrode material.
[0066] Figure 1 A schematic diagram showing the formation process of the sodium ion positive electrode material provided in Example 1 is shown, from Figure 1 It can be seen that after the hydroxide precursor is modified by the surfactant and subsequently mixed with the polymer material and then sintered, a tightly bonded oxygen-depleted layer is obtained.
[0067] Example 2
[0068] This embodiment provides a sodium ion positive electrode material, the positive electrode material comprises a sodium ion layered oxide core and an oxygen-deficient layer located on the surface of the core, the chemical formula of the sodium ion layered oxide core is Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2, the oxygen-depleted layer has a rock salt phase structure and is in situ constructed on the surface of the layered oxide, that is, the oxygen-depleted layer is an oxygen-depleted phase containing Na, Ni, Fe and Mn.
[0069] The preparation method of the sodium ion positive electrode material is as follows:
[0070] (1) The sulfates corresponding to the required elements (NiSO4, MnSO4, FeSO4) are divided into Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2 is dissolved in a stoichiometric ratio into a solution, which is marked as solution A; a NaOH solution (precipitant solution) and an ammonia solution (NH3·H2O) solution (complexing agent solution) are prepared; solution A, the precipitant solution and the complexing agent solution are added to a continuous reactor in parallel, the pH value during the reaction is controlled to be 9, a coprecipitation reaction is carried out at a reaction temperature of 50°C and a rotation speed of 800r / min, the solution after the reaction is aged for 5h, and the target precursor Ni is obtained after multiple washings with deionized water and drying. 0.6 Fe 0.25 Mn 0.15 (OH)2;
[0071] (2) 100g of precursor Ni 0.6 Fe 0.25 Mn 0.15 (OH)2 was dispersed in water, 1 g of polyvinyl pyrrolidone (PVP) was added, ultrasonicated for 20 min, then stirred for 25 min, dopamine was added (the amount of dopamine added was 6% of the precursor material), stirred for 6 h, filtered, and dried in a drying oven at 80 ° C for 8 h to obtain a dopamine-coated precursor material;
[0072] (3) The precursor material in step (2) is uniformly mixed with Na2CO3 in a stoichiometric ratio, sintered at 550°C for 4 hours in an oxygen atmosphere, and then heated to 850°C for a second sintering for 12 hours to obtain the sodium ion positive electrode material.
[0073] Example 3
[0074] This embodiment provides a sodium ion positive electrode material, the positive electrode material comprises a sodium ion layered oxide core and an oxygen-deficient layer located on the surface of the core, the chemical formula of the sodium ion layered oxide core is Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2, the oxygen-depleted layer has a rock salt phase structure and is in situ constructed on the surface of the layered oxide, that is, the oxygen-depleted layer is an oxygen-depleted phase containing Na, Ni, Fe and Mn.
[0075] The preparation method of the sodium ion positive electrode material is as follows:
[0076] (1) The sulfates corresponding to the required elements (NiSO4, MnSO4, FeSO4) are divided into Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2 is dissolved in a stoichiometric ratio into a solution, which is marked as solution A; a NaOH solution (precipitant solution) and an ammonia solution (NH3·H2O) solution (complexing agent solution) are prepared; solution A, the precipitant solution and the complexing agent solution are added to a continuous reactor in parallel, the pH value during the reaction is controlled to be 9, a coprecipitation reaction is carried out at a reaction temperature of 50°C and a rotation speed of 800r / min, the solution after the reaction is aged for 5h, and the target precursor Ni is obtained after multiple washings with deionized water and drying. 0.6 Fe 0.25 Mn 0.15 (OH)2;
[0077] (2) 100g of precursor Ni 0.6 Fe 0.25 Mn 0.15 (OH)2 was dispersed in water, 2 g of polyvinyl pyrrolidone (PVP) was added, ultrasonicated for 30 min, then stirred for 30 min, dopamine was added (the amount of dopamine added was 2% of the precursor material), stirred for 6 h, filtered, and dried in a drying oven at 80 ° C for 8 h to obtain a dopamine-coated precursor material;
[0078] (3) The precursor material in step (2) is uniformly mixed with Na2CO3 according to a stoichiometric ratio, sintered at 500°C for 5 hours under an oxygen atmosphere, and then heated to 750°C for a second sintering for 20 hours to obtain the sodium ion positive electrode material.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that the amount of dopamine added in step (2) of this embodiment is 4% of the precursor material.
[0081] The rest of the preparation methods and parameters were the same as those in Example 1.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 1 is that the amount of dopamine added in step (2) of this embodiment is 5% of the precursor material.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that the amount of dopamine added in step (2) of this embodiment is 1% of the precursor material.
[0087] The rest of the preparation methods and parameters were the same as those in Example 1.
[0088] Example 7
[0089] The difference between this embodiment and embodiment 1 is that the amount of dopamine added in step (2) of this embodiment is 7% of the precursor material.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, PVP is mixed with dopamine and precursor materials at the same time.
[0093] The rest of the preparation methods and parameters were the same as those in Example 1.
[0094] Example 9
[0095] The difference between this embodiment and embodiment 1 is that PVP is not added in step (2) of this embodiment.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Example 10
[0098] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, urea is used to replace dopamine (the amount of urea added is 7.8% of the precursor material).
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Embodiment 11
[0101] The difference between this embodiment and embodiment 10 is that the amount of urea added in step (2) of this embodiment is 5% of the precursor material.
[0102] The rest of the preparation methods and parameters were the same as those in Example 10.
[0103] Example 12
[0104] The difference between this embodiment and embodiment 10 is that the amount of urea added in step (2) of this embodiment is 1% of the precursor material.
[0105] The rest of the preparation methods and parameters were the same as those in Example 10.
[0106] Embodiment 13
[0107] The difference between this embodiment and embodiment 1 is that the chemical formula of the sodium ion layered oxide core in this embodiment is NaNi 0.16 Fe 0.16 Mn 0.68 O2.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 1 is that this comparative example does not carry out step (2), that is, step (3) is carried out directly after obtaining the precursor material.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 1 is that the preparation method of this comparative example is as follows:
[0114] (1) The sulfates corresponding to the required elements (NiSO4, MnSO4, FeSO4) are divided into Na(Ni 0.6 Fe 0.25 Mn 0.15 )O2 is dissolved in a solution in a stoichiometric ratio, which is marked as solution A; a NaOH solution (precipitant solution) and an ammonia solution (NH3·H2O) solution (complexing agent solution) are prepared; solution A, the precipitant solution and the complexing agent solution are added to a continuous reactor in parallel, the pH value during the reaction is controlled to be 8.5, a coprecipitation reaction is carried out at a reaction temperature of 50°C and a rotation speed of 1000r / min, the solution after the reaction is aged for 5h, and the target precursor Ni is obtained after multiple washings with deionized water and drying. 0.6 Fe 0.25 Mn 0.15 (OH)2;
[0115] (2) uniformly mixing the precursor material in step (1) with Na2CO3 according to a stoichiometric ratio, and sintering at 450°C for 5 hours under an oxygen atmosphere to obtain a fired material;
[0116] (3) 100 g of the calcined material was dispersed in water, 1 g of polyvinyl pyrrolidone (PVP) was added, ultrasonicated for 20 min, then stirred for 25 min, dopamine was added (the amount of dopamine added was 1% of the calcined material), stirred for 6 h, filtered, dried in a drying oven at 80 ° C for 8 h, and then heated to 900 ° C for secondary sintering for 20 h to obtain the sodium ion positive electrode material.
[0117] Comparative Example 3
[0118] The difference between this comparative example and Example 13 is that this comparative example does not carry out step (2), that is, step (3) is carried out directly after obtaining the precursor material.
[0119] The rest of the preparation methods and parameters were consistent with those in Example 13.
[0120] The sodium ion positive electrode materials conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) provided in Example 1-13 and Comparative Example 1-3 were mixed in a mass ratio of 8:1:1 to obtain a slurry, which was then coated on aluminum foil to form a positive electrode sheet. The prepared positive electrode sheet and the sodium metal sheet were assembled into a sodium ion button cell, and sodium perchlorate with a concentration of 1M was dissolved in polycarbonate (PC) / fluoroethylene carbonate (FEC) (mass ratio 97:3, Shenzhen Youyan) to obtain an electrolyte. After the button cell assembly was completed, the capacity and cycle tests were performed as follows: standing for 2h; constant current charge and discharge, the charge and discharge voltage range was 2.0-4.0V, the cycle rate was 0.5C, 2.0C, and the rated gram capacity was 120mAh / g. The test results are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] From the data results of Examples 1-5 and Examples 6-7, it can be seen that if too little dopamine is added, it is not conducive to forming a uniform and continuous protective layer, part of the main material cannot be covered, and continuous and effective protection cannot be provided to the material. Therefore, the cycle stability cannot be effectively improved. If too much dopamine is added, the thickness of the oxygen-depleted layer will be too large, affecting the electrochemical properties of the material. The specific capacity, rate performance and stability of the main material are also affected.
[0125] From the data results of Example 1 and Example 8, it can be seen that if the surfactant is not added first to modify the precursor material but is mixed with the polymer material at the same time, the added polymer material cannot form a uniform and effective coating on the surface of the material, so that the obtained oxygen-deficient phase layer will have an uneven coating, resulting in poor electrochemical performance of the sodium ion positive electrode material.
[0126] From the data results of Example 1 and Example 9, it can be seen that if a surfactant is not added for modification during the mixed coating process of the polymer material on the precursor material, it is not conducive to the formation of a uniform and continuous coating layer. The polymer material will agglomerate to a certain extent during the mixing process, which will affect the formation of a continuous oxygen-deficient phase protective layer during the sintering process and is not conducive to the improvement of the electrochemical performance.
[0127] From the data results of Example 1, Example 10 and Comparative Example 1, it can be seen that the surface of the sodium ion positive electrode material does not contain an oxygen-depleted layer, and it is impossible to effectively protect the bulk material during the cycle, resulting in poor material cycle performance and low specific capacity at high rates. After the oxygen-depleted layer is introduced, effective protection can be provided to the bulk material during the cycle, the specific capacity of the material under high-rate charge and discharge conditions can be increased, and the cycle performance of the material can be significantly improved.
[0128] From the data results of Example 1 and Comparative Example 2, it can be seen that the surface of the precursor material obtained by the co-precipitation method is first coated and then sintered and oxidized to form a uniform and continuous oxygen-deficient phase protective layer. However, when the sodium ion material is directly coated and then sintered, due to the influence of water on Na2CO3 or Na2O, a normal bulk material cannot be formed, and the material performance is lower than the normal level in Comparative Example 1.
[0129] In summary, the present invention modifies the sodium ion hydroxide precursor material with a polymer material to form a composite structure with the polymer material. In the subsequent sintering process in an oxygen-containing atmosphere, the carbonization and oxidation process of the polymer will in situ construct an oxygen-deficient layer on the surface of the sodium ion layered oxide that is tightly combined with the main material and has a stable structure, thereby achieving the effect of improving the rate performance and the cycle stability at different rates. When the battery adopts the sodium ion positive electrode material provided by the present invention, the amount of dopamine added is 2-6% of the mass of the sodium ion hydroxide precursor, or the amount of urea added is 0-8% of the mass of the sodium ion hydroxide precursor and does not include 0%, the capacity retention rate after 100 cycles at 0.5C can reach more than 80.3%, and the capacity retention rate after 300 cycles at 2C can reach more than 59.6%.
[0130] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion positive electrode material, characterized in that: The positive electrode material comprises a sodium ion layered oxide core and an oxygen-deficient layer located on the surface of the core, wherein the oxygen-deficient layer is a rock salt phase structure; The sodium ion positive electrode material is obtained by the following preparation method, which comprises the following steps: (1) mixing and coating a sodium ion hydroxide precursor with a polymer material to obtain a precursor of a surface-coated polymer material; (2) Mixing the precursor of the surface-coated polymer material of step (1) with a sodium source, and sintering them in an oxygen-containing atmosphere to obtain the sodium ion positive electrode material.
2. The sodium ion positive electrode material according to claim 1, characterized in that The chemical formula of the sodium ion layered oxide core is NaNi x M y Mn z O2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
3. A method for preparing a sodium ion positive electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing and coating a sodium ion hydroxide precursor with a polymer material to obtain a precursor of a surface-coated polymer material; (2) Mixing the precursor of the surface-coated polymer material of step (1) with a sodium source, and sintering them in an oxygen-containing atmosphere to obtain the sodium ion positive electrode material.
4. The method for preparing the sodium ion positive electrode material according to claim 3, characterized in that: The chemical formula of the sodium hydroxide precursor in step (1) is Ni x M y Mn z (OH)2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
5. The method for preparing the sodium ion positive electrode material according to claim 3, characterized in that: The method for preparing the sodium ion hydroxide precursor in step (1) comprises: A mixed salt solution of a nickel source, a manganese source and an M source, a precipitant solution and a complexing agent solution are added in parallel to carry out a coprecipitation reaction and age to obtain the sodium ion hydroxide precursor, wherein the M source includes any one of a cobalt source, an iron source, a copper source, a titanium source or a tin source or a combination of at least two thereof.
6. The method for preparing the sodium ion positive electrode material according to claim 5, characterized in that: The reaction temperature during the coprecipitation reaction is 40-60°C.
7. The method for preparing a sodium ion positive electrode material according to claim 5, characterized in that: The rotation speed during the coprecipitation reaction is 800-1200 r / min.
8. The method for preparing a sodium ion positive electrode material according to claim 5, characterized in that: The pH value during the coprecipitation reaction is 8-10.
9. The method for preparing a sodium ion positive electrode material according to claim 5, characterized in that: The aging time is 3 to 7 hours.
10. The method for preparing a sodium ion positive electrode material according to claim 3, characterized in that: In step (1), the mass of the polymer material is 0 to 10% of the mass of the sodium ion hydroxide precursor, excluding 0%.
11. The method for preparing a sodium ion positive electrode material according to claim 3, characterized in that: The elements in the polymer material include C and H.
12. The method for preparing a sodium ion positive electrode material according to claim 11, characterized in that: The elements in the polymer material also include O and / or N.
13. The method for preparing a sodium ion positive electrode material according to claim 12, characterized in that: The polymer material includes any one of urea, dopamine, glucose, sucrose or tannic acid, or a combination of at least two of them.
14. The method for preparing a sodium ion positive electrode material according to claim 13, characterized in that: The mass of the urea is 0 to 8% of the mass of the sodium ion hydroxide precursor, excluding 0%.
15. The method for preparing a sodium ion positive electrode material according to claim 13, characterized in that: The mass of the dopamine is 2-6% of the mass of the sodium ion hydroxide precursor.
16. The method for preparing a sodium ion positive electrode material according to claim 3, characterized in that: The mixed coated raw materials in step (1) also include a surfactant.
17. The method for preparing a sodium ion positive electrode material according to claim 16, characterized in that: The mass of the surfactant is 1-3% of the mass of the sodium ion hydroxide precursor.
18. The method for preparing a sodium ion positive electrode material according to claim 16, characterized in that: The surfactant includes polyvinyl pyrrolidone and / or cetyltrimethylammonium bromide.
19. The method for preparing a sodium ion positive electrode material according to claim 16, characterized in that: When a surfactant is included in the mixed coating process of step (1), the mixed coating comprises: Firstly, a sodium ion hydroxide precursor is mixed with a surfactant, and then a polymer material is added for mixed coating.
20. The method for preparing a sodium ion positive electrode material according to claim 3, characterized in that: The sintering in step (2) includes performing primary sintering and secondary sintering in sequence.
21. The method for preparing a sodium ion positive electrode material according to claim 20, characterized in that: The primary sintering temperature is 450-550°C.
22. The method for preparing a sodium ion positive electrode material according to claim 20, characterized in that: The temperature of the secondary sintering is 750-900°C.
23. The method for preparing a sodium ion positive electrode material according to claim 3, characterized in that: The preparation method comprises the following steps: (1) adding a mixed salt solution of a nickel source, a manganese source and an M source, a precipitant solution and a complexing agent solution in parallel, performing a coprecipitation reaction at 40 to 60° C. and a rotation speed of 800 to 1200 r / min, wherein the pH value during the reaction is 8 to 10, and aging is performed for 3 to 7 hours to obtain a sodium ion hydroxide precursor; Firstly, a sodium ion hydroxide precursor is mixed with a surfactant, wherein the mass of the surfactant is 1 to 3% of the mass of the sodium ion hydroxide precursor, and then a polymer material is added for mixed coating, wherein the mass of the polymer material is 0 to 10% of the mass of the sodium ion hydroxide precursor but does not include 0%, to obtain a precursor with a surface coated with the polymer material; (2) mixing the precursor of the surface-coated polymer material of step (1) with a sodium source, and sequentially performing primary sintering and secondary sintering in an oxygen-containing atmosphere to obtain the sodium ion positive electrode material; Wherein, the chemical formula of the sodium hydroxide precursor in step (1) is Ni x M y Mn z (OH)2, wherein 0<x<1, 0<y<1, 0<z<1, x+y+z=1, and M includes any one of Co, Fe, Cu, Ti or Sn or a combination of at least two thereof.
24. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion positive electrode material as claimed in claim 1 or 2.
Citation Information
Patent Citations
Coating-structure sodium-ion battery anode material as well as preparation method and application thereof
CN109524649A
Coating method of sodium ion battery positive electrode material and secondary battery thereof
CN109638273A
Controllable epitaxial sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN114597363A
Cathode materials for secondary batteries
US20210280863A1